2018
DOI: 10.1530/ec-17-0242
|View full text |Cite
|
Sign up to set email alerts
|

Exenatide treatment causes suppression of serum fasting ghrelin levels in patients with type 2 diabetes mellitus

Abstract: AimIn the present study, we investigated the long-term effects of exenatide treatment on serum fasting ghrelin levels in patients with type 2 diabetes mellitus.MethodsType 2 diabetic patients, who were using metformin with and without the other antihyperglycemic drugs on a stable dose for at least 3 months, were enrolled in the study. BMI>35 kg/m2 and HbA1c>7.0% were the additional inclusion criteria. Oral antihyperglycemic drugs, other than metformin, were stopped, and metformin treatment was continued at 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…There are several animal studies examining the effects of exenatide on ghrelin. In one of the limited studies examining the effect of exenatide use on ghrelin in type 2 diabetics, a decrease was found in ghrelin levels measured after 3 months of exenatide therapy similar to our study (4). Other studies generally reported the acute effects on ghrelin.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…There are several animal studies examining the effects of exenatide on ghrelin. In one of the limited studies examining the effect of exenatide use on ghrelin in type 2 diabetics, a decrease was found in ghrelin levels measured after 3 months of exenatide therapy similar to our study (4). Other studies generally reported the acute effects on ghrelin.…”
Section: Resultssupporting
confidence: 89%
“…Exenatide requires two injections a day and is more effective in lowering postprandial glycemia and provides an average weight loss of 2-4 kilograms unlike other anti-hyperglycemic drugs and insulin (3). It has been shown that exenatide lowers ghrelin and FGF21 levels in a small number of studies conducted in type 2 diabetic patients but there is no study in the literature regarding the effect of GDF-15 which is considered to be as another metabolic regulator (4,5).…”
Section: Introductionmentioning
confidence: 99%